algebra URGENT HELP

posted by .

A)p(x)= x(x+2)(x-4)


b)p(x)=(x+2)^3(x-1)

  • algebra URGENT HELP -

    what is the question?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math urgent urgent urgent

    1)let f(x) be a polynomial function explian how to use the factor theorem to check if (x-c) is a factor of F(x) 2) use synthetic division to factor X^2-2x^2-9x+18 completly
  2. math urgent urgent urgent

    perpendicular to line -2x+y=7 contains the point (-4,-2) the equation of line is
  3. math urgent urgent urgent

    x+2y=12 find intercept a circle equation x^2+y^2+4x-4y-1=0 and graph 2)find domain and range f(x)=x^2-4x-5 find vertex of f(x) =x^2+4x-21
  4. urgent urgent urgent

    A freshman studying medicine at an Ivy League College is a part of his class crew team and exercises regularly. After a particularly strenuous exercise session, he experiences severe cramps in his thighs and pain in his biceps. explain …
  5. urgent urgent urgent

    A freshman studying medicine at an Ivy League College is a part of his class crew team and exercises regularly. After a particularly strenuous exercise session, he experiences severe cramps in his thighs and pain in his biceps. •Explain …
  6. urgent urgent urgent

    what is the chemical make up of actin and myocin
  7. urgent urgent algebra

    find the composite function fog f(X) = 1/X-5,g(x)-6/x question 2 find inverse, domain range and asymatotes of each function f(x)=3+e^4-x can some one help me please been stuck on these for 2 days need help solving thank you
  8. urgent urgent algebra

    rewrite each in exponential expression as a logarithmic expression a)log,x=4 b)log 5=2 c)log ,8=x
  9. urgent urgent algebra / precalculas

    rewrite each in exponential expression as a logarithmic expression log, x=4 log 5=2 log b=x
  10. urgent urgent algebra / precalculas

    1. Given a function,H(x)explain how to find the components f(X)AND g(x) such that f(g(x)) = H(x) 2. let H(x)=(2x+5)^4 find the function f and , so that f(g(X))=H(x)

More Similar Questions